2022
DOI: 10.1155/2022/8938276
|View full text |Cite
|
Sign up to set email alerts
|

Type 2 Diabetic Mellitus Inhibits Skin Renewal through Inhibiting WNT-Dependent Lgr5+ Hair Follicle Stem Cell Activation in C57BL/6 Mice

Abstract: Background. Hair follicles are important accessory organs of the skin, and it is important for skin renewal and performs variety of important functions. Diabetes can cause several dermatoses; however, its effect on hair follicles is unclear. The purpose of this study was to investigate the effect of type II diabetes (T2DM) on the hair follicles of mice. Methods. Seven-week-old male C57BL/6 littermate mice were divided into two groups. The treatment group was injected with streptozotocin (STZ) to induce T2DM, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 54 publications
0
10
0
Order By: Relevance
“…Then, slides were stained with hematoxylin-eosin (H&E). Details are as described in the previous studies [ 16 , 17 ]. Histological changes were observed under a microscope (DM2500, Leica, Germany).…”
Section: Methodsmentioning
confidence: 99%
“…Then, slides were stained with hematoxylin-eosin (H&E). Details are as described in the previous studies [ 16 , 17 ]. Histological changes were observed under a microscope (DM2500, Leica, Germany).…”
Section: Methodsmentioning
confidence: 99%
“…Alopecia areata, one of the autoimmune diseases, shows reduced Wnt/β-catenin signaling that causes hair loss ( 16 ). Furthermore, there have been case studies of increased hair loss in diabetic patients ( 38 ) and reports of the hair growth inhibition by inactivated Wnt/β-catenin signaling in diabetes ( 8 ). Thus, our findings together with the importance of regulating the Wnt/β-catenin signaling pathway in several chronic diseases suggest that Wnt activators might be potential therapeutic agents for patients with several chronic diseases, including diabetic alopecia.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, diabetic retinopathy is caused by up-regulation of Wnt/β-catenin signaling ( 5 ), whereas diabetic foot ulcer and diabetes-related Alzheimer’s diseases are caused by down-regulation of Wnt/β-catenin signaling ( 6 , 7 ). A recent study has shown that diabetes can inhibit hair regrowth by inhibiting Wnt/β-catenin signaling ( 8 ). However, this study was mainly focused on the effect of diabetes on hair follicle cycle transition, not on hair follicle neogenesis itself, using a hair depilation model.…”
Section: Introductionmentioning
confidence: 99%
“…The hair follicle (HF), sebaceous gland and sweat gland, namely the appendage of the skin are derived from a single layer of multipotent progenitors during skin morphogenesis [ 1 ]. HFs are important cutaneous appendages that maintain skin function and self-renewal [ 2 ]. In postpartum humans, however, deep injuries to the skin heal with scar formation but do not regenerate, and the epidermal appendages lost at the injury site do not regenerate [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the gut, Lgr5 cells are not necessary for gut homeostasis [ 18 ], but they are essential for intestinal regeneration after radiation [ 19 ]. Similarly, Lgr5 HFSCs are necessary for hair regeneration and wound healing but not for homeostasis [ 2 , 20 ]. Depletion of Lgr5 HFSCs inhibits hair regeneration; however, this phenomenon is reversible [ 21 ].…”
Section: Introductionmentioning
confidence: 99%